Literature survey on motion estimation techniques - Mahaboob Basha, S; Kannan, M (International Journal of Engineering and Technology, 2018)
Motion Estimation (ME) is one of the most intensive computational operations in video compression techniques. Video compression algo-rithm utilizes numerous standards such as MPEG1, MPEG4 AND H.261, H.264. Compression performance can be increased drastically by efficient motion estimation techniques by which energy is reduced within the residual frames involved in motion compensation. In this paper literature survey of motion estimation especially considering block matching ME (Motion Estimation). In this paper, comparison is made between the already existing block matching algorithms and their limitations in motion estimation along with their applications. Many algorithms including Three Step Search (TSS), Improved Three Step Search (ITSS), New Three Step Search (NTSS), Four Step Search (4SS), Diamond Search (DS), Flexible Triangle Search(FTS), Full Search(FS), Modified Full Search(MDF) are compared and their per-formance measures are discussed in this paper.Â Â